IMPLEMENTING INTEGRATED STRATEGIES IN ENGLISH CLASSES: CHALLENGES AND OUTCOMES - Hamroyeva Zilola Hikmatovna,; Yuldasheva Gulmira Kamolovna, (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract.  This  article  explores  the  effectiveness  of  integrated  education  for students in English language classes, examining how a holistic approach to teaching can enhance language and cognitive development. Integrated education refers to the incorporation of diverse teaching strategies that blend language learning with content instruction, promoting critical thinking, problem-solving, and collaborative learning. The study reviews various pedagogical frameworks, including Content and Language Integrated  Learning  and  task-based  approaches,  to  assess  their  impact  on  student engagement,  language  acquisition,  and  academic  performance.  Drawing  from empirical research and case studies, the article highlights the benefits and challenges of integrating subjects and language learning, suggesting that such an approach fosters a  more  inclusive,  interactive,  and  student-centered  educational  environment. Ultimately,  the  findings  demonstrate  that  integrated  education  in  English  classes contributes to improved learning outcomes, greater student motivation, and a deeper understanding of both language and content.